Hybrid Identity in Academic Writing: "Are There Two of Me?" - Troy Crawford; Martha Lengeling; Irasema Mora Pablo; Rocío Heredia Ocampo (Universidad Nacional de Colombia, 2014)
This paper explores the construction of identity in an academic learning environment in Central Mexico, and shows how identity may be linked to non-language factors such as emotions or family. These issues are associated with elements of hybrid identity. To analyze this we draw on language choice as a tool used for the construction of identity and for showcasing and defending identity through exploratory interviews with the bilingual students and teachers. The results draw our attention towards the role of non-linguistic variables and their relationship to emotional and contextual issues that influence how academic writing occurs within the school confines, where hybrid identities may be constructed for academic purposes.